Different findings of morphological changes and functional decline in the vestibule and the semicircular canal in ipsilateral delayed endolymphatic hydrops. Issue 7 (July 2020) - Yu, Jing; Zhou, Yu-Juan; Xu, Xin-Da; Tian, Liang; Ren, Dong-Dong; Ding, Chen-Ru; Wang, Jing; Chi, Fang-Lu
Highlights: Hydrops can be found mainly in the vestibule as shown by MRI. In the vestibule, abnormalities are commonly morphologic rather than functional. In the lateral semicircular canal, a functional deterioration can be detected more frequently than morphological changes. Abstract: Objective: To elucidate the pathophysiological process by analyzing the correlation between morphological and functional changes in patients with delayed endolymphatic hydrops (DEH). Methods: Twenty-nine patients diagnosed with DEH were enrolled in this retrospective study. All patients were assessed using the caloric test, cervical and ocular vestibular evoked myogenic potentials, and gadolinium-enhanced magnetic resonance imaging (MRI) of the inner ear. Results: According to the MRI, the hydrops localization was categorized as hydrops in the vestibule (saccule and utricle) (14%), hydrops in the vestibule and cochlea (72%), and hydrops in the vestibule, cochlea, and lateral semicircular canal (LSCC) (14%). Vestibular hydrops could definitely be observed as function declined; however, a dysfunction of both the saccule and utricle was not always present when vestibular hydrops was detected with MRI. In the LSCC, a decline in functional tests was not necessarily accompanied by morphological abnormalities. However, dysfunction could definitely be detected when LSCC hydrops was observed with MRI. Conclusions: Hydrops can be found mainly in the vestibule as shown by MRI. In the vestibule, abnormalities are commonly morphologic rather than functional, whereas in the LSCC a functional deterioration can be detected more frequently than morphological changes. Significance: Our findings can provide a new perspective on the functional and morphological characteristics of patients with DEH.